Multisensory Stimulation in Stroke Rehabilitation - Johansson, Barbro B. (Frontiers in Human Neuroscience, 2012)
The brain has a large capacity for automatic simultaneous processing and integration of sensory information. Combining information from different sensory modalities facilitates our ability to detect, discriminate, and recognize sensory stimuli, and learning is often optimal in a multisensory environment. Currently used multisensory stimulation methods in stroke rehabilitation include motor imagery, action observation, training with a mirror or in a virtual environment, and various kinds of music therapy. Non-invasive brain stimulation has showed promising preliminary results in aphasia and neglect. Patient heterogeneity and the interaction of age, gender, genes, and environment are discussed. Randomized controlled longitudinal trials starting earlier post-stroke are needed. The advance in brain network science and neuroimaging enabling longitudinal studies of structural and functional networks are likely to have an important impact on patient selection for specific interventions in future stroke rehabilitation. It is proposed that we should pay more attention to age, gender, and laterality in clinical studies.